(untitled) (Asian Journal of Social Science Studies, 2026)
Anita 《梅艳芳》 is a biopic newly released in 2021, chronicling her journey from a child performer to one of most recognized music idols in China and Southeast Asia. Mui began her singing career as a little girl, giving shows at an amusement park. Known as “Asian Madonna”, she kicked off her career by winning a singing contest in Hong Kong in 1982. Meanwhile, Mui also gained fame as an actress. She starred in more than 40 movies over 20 years, winning Taiwan’s Golden Horse award for best actress in 1987 for her role as a tormented ghost in the movie “Rouge.” She was also known for her charity work, setting up the Anita Mui Charity Foundation in 1990s. Biopics generally focus on a non-fictional or historical person, reflecting the characteristics of the social context by retelling his or her life story in a comprehensive way. Thus, the protagonist Mui and the context she lived in make Anita a special Chinese biopic. Anita Mui lived in Hong Kong from 1963 to 2003, and she is known as “The Daughter of Hong Kong” for the spirits and culture reflected by her life story. Different from most Chinese biopics, the protagonist in this film is a female, not a male like Ip Man, Wong Fei Hung or Mei Lang Fang in most Chinese biopic. Besides, Mui is a modern singer, not a patriotic heroine such as Qiu Jin and Liu Hu Lan, or a feudal empress such as imperial concubine Yang (杨贵妃) and Empress Wu. In a survey of biography up to 1960, George Custen finds that female biopic subjects in the thirties were often queens The image of Mui as a modern female is complex and multi-dimensional. She is traditional in some way, shouldering heavy family burden, expressing her wish for marriage, while her works broke the common impressions toward female at that time. For example, songs like “Bad Girl” caused a ruckus in 1985 with its brazen lyrics about female sexual desire. She openly revealed her wish for romantic relationship and marriage life by saying “My idol is Momie Yamaguchi, who resolutely decide to retire at the height of her career for the one she love”, while at the same time, she presented herself as an independent singer, actress and a philanthropist, revealing her feeling that “I will concentrate on my career development in these years and I don‟t need to settle down yet”. To sum up, Mui‟s life story reflects the muti-dimensional values and dilemmas of Chinese career woman, which makes Anita a special biopic in China.